Measuring democracy among ordinary citizens—Challenges to studying democratic ideals - Refle, Jan-Erik (Frontiers in Political Science, 2022)
The article addresses the methodological challenges in measuring democratic ideals on an individual level in quantitative studies. Building upon own empirical research, the study identifies several difficulties in assessing individuals’ attitudes on democracy. In addition to a discussion of quantitative measures on individual-level data such as the ESS module on democracy or the Afrobarometer measures, the study assesses the possibility of other endeavors and what these look like. The study identifies multidimensionality, the association between elements, as well as problems in aggregating concepts, as important elements to be addressed in research. In the last step, certain quantitative measures are tested through a survey to show possible solutions to the issues.